Preceptorship: host of the student in the basic health care (Research, Society and Development, 2019)
This article presents an integrative literature review about preceptorship and the reception of health's students in primary health care. The objective was to verify how preceptors welcome students during their internship, and how they receive the information for a better use of the internship. CAPES Journal website was used to access LILACS and SCIELO databases where 48 studies were found, published between 2005 and 2015. The inclusion criteria were original studies that mentioned preceptorship, actuation of preceptors and the reception of students during internship. The exclusion criteria were literature review, reflexive texts, duplicate articles and summaries. After analysis, 38 studies were excluded, remaining 10 studies. In the studies used different forms of reception were found to the undergraduate student, but no document that the preceptors can follow to receive the student. Through this work it's possible to see the need of more studies and publications that would help the preceptors, so that they can have a theoretical basis for the reception of the students who will carry out the internship, helping in a better use and development of the same.